Inkonsistensi Asas Legalitas dalam Rancangan Kitab Undang-Undang Hukum Pidana 2005 - Alfons Zakaria (Fakultas Hukum Universitas Mulawarman, 2006)
One of fundamental principles in criminal law is principle of legality. According to this principle, no felony shall be punishable by any penalty not prescribed by law prior to its commission. This principle has the meaning that the criminal act must be explicitly mentioned in the law. In other words, the law must be in written and the criminal act also must be written in detail in the law before the criminal act done. Another meaning of this principle are retroaktif principle and analogical interpretation are unable to be implemented. So that unwritten living law is not ricognized in this principle. Key words: asas legalitas (principle of legality), hukum yang hidup dalam masyarakat (the living law)